THE EFFECT OF MAULI BANANA (Musa acuminata) STEMS AND BASIL LEAVES (Ocimum basilicum) EXTRACTS ON GIC DISCOLORATION - Norhayati Norhayati; Sherli Diana; Rosihan Adhani (Dentin, 2023)
Background: The water settable GIC material is easily influenced by fluids and is hydrophilic which causes discoloration of the restoration. Chlorhexidine is the gold standard mouthwash and if used for a long period of time it can cause discoloration of the restoration because it contains chemicals, so an alternative mouthwash made from natural ingredients is needed. A mixture of mauli banana stem and basil leaves extract has a more optimal antibacterial ability. Objective: In general, this study aimed to analyze the effect of a mixture of Mauli banana stem (Musa acuminata) and basil leaves (Ocimum basilicum) extracts on discoloration of the water settable GIC. Methods: This research is a true experimental research with pre test and post test designs with control group design. This study was divided into three treatments, namely water settable GIC soaked in a mixture of extracts of banana stems and basil leaves at concentrations of 75%, 100%, and 0.2% chlorhexidine gluconate (positive control). Color measurement was carried out using a series of digital analysis tools consisting of a Samsung A1 macro camera, Peyond series PD-480 SL and the MATLAB application. Results: The results of the Kruskal-Wallis statistical test showed p value = 0.282 (> 0.05), meaning that there was no significant difference in color change between the three treatments. Conclusion: There is an effect of a mixture banana mauli stems (Musa acuminata) and basil leaves (Ocimum basilicum) extracts at concentrations of 75%, 100%, and 0.2% chlorhexidine gluconate on the discoloration of the water settable GIC. Keywords: Basil leaves (Ocimum basilicum), CIELAB system, discoloration, mauli banana stem (Musa acuminata), water settable GIC